A preliminary evaluation of a single session behavioural activation intervention to improve well-being and prevent depression in carers - Read, A.; Mazzucchelli, Trevor; Kane, Robert (Wiley-Blackwell Publishing Ltd., 2016)
Background: Major depressive disorder is predicted to be the lead cause of disease burden by 2030. Despite evidence suggesting that major depressive disorder can be prevented, little attention has been paid to developing interventions for this purpose. As research suggests that high levels of subjective well-being may protect against depression, an intervention that can enhance and maintain subjective well-being may assist in preventing major depressive disorder. Behavioural activation (BA) is a promising intervention that has been observed to both effectively treat depression and also enhance subjective well-being, even in a single session. Method: A randomised control design was used to investigate the efficacy of a single session of BA to boost well-being and reduce distress in a community sample of carers (N = 13), who may be at increased risk of major depressive disorder. Outcome measures assessed symptoms of depression, anxiety, stress, and well-being and the lifestyle factors of perceived environmental reward and the extent to which individuals lived in accordance with their personal values. Results: Generalised linear mixed modelling revealed significant group × time interactions for stress scores and valued living, indicating a treatment effect on these outcomes. Conclusions: Findings provide preliminary support for the effectiveness of a single session BA intervention to improve outcomes of carers.